Correct and effective use of modern methods of teaching technology education (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the tasks and teaching of the science of technology methods are discussed. In addition, the purpose of this science and about the impact of science on young students. Learning this science any accident that will happen in the life of the student’s preparation for events is provided.